RISK STRATIFICATION OF MENTAL DISORDERSON A BASIC HEALTH UNIT FROM THE CITY OF TERRA ROXA / PR (Fiep Bulletin - online, 2016)
The aim of this field research is to characterize the mental health disorders of an enrolled population using the methodology to risk stratification in health implemented by the federal government in all Brazilian states and cities. The study subjects were individuals diagnosed with mental disorders registered at the Health Family Unit, downtown. As a result, the survey was carried out with mentally ill people registered at the health unit of the city of Terra-Roxa – PR. The disease has reached 67% women and 33% men being interviewed from the age of 0 to over 79 years old, and 29% of the disease has reached the age group between 60-79 years and other values distributed among other age groups. A great number of 67% with low education considering being illiterate and 33% completed high school. 98% of the interviewees have a household income, being minimum wage, assistance illness or retirement and 2% with no income. The barrier between the mentally ill and family was clear through the interview. 14% of respondents do not consider themselves sick so they do not seek treatment and other 86% follow some treatment and the medical follow-up with return appointments is established according to the stabilization of the clinical picture and the patient's need. All respondents use psychotropic medications and the majority (34%) use antidepressants. Only 9% carry therapeutic activity while 91% does not know it. The final results concluded that 33% of the population is in the low level of the disease and the other 67% is in medium and high level of disease.
Keywords: Mental Health; Quality of Service; Benefit.